2013
DOI: 10.4209/aaqr.2012.06.0155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Particles in the Ambience of the High-Tech Industrial Park of Central Taiwan

Abstract: Medical scholars have confirmed that prolonged exposure to high concentrations of suspended particles may result in respiratory and heart diseases. To identify the characteristics of particles around high-tech industrial parks, engaged in the manufacturing of semiconductors, electronics and electrical peripherals, this study performed a two-year monitoring program to measure the heavy metal composition in airborne particles in order to find the potential sources of pollution as well as the causal relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Among these environmental problems caused by mining activities, the production and dispersion of atmospheric particles has become a great concern in recent years (Kaonga and Kgabi 2011;Chen et al 2013;Serbula et al 2014). Atmospheric particulates are generated from numerous sources, both natural and anthropogenic, but in areas near mining, mining operations are considered the largest contributor.…”
Section: Introductionmentioning
confidence: 99%
“…Among these environmental problems caused by mining activities, the production and dispersion of atmospheric particles has become a great concern in recent years (Kaonga and Kgabi 2011;Chen et al 2013;Serbula et al 2014). Atmospheric particulates are generated from numerous sources, both natural and anthropogenic, but in areas near mining, mining operations are considered the largest contributor.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the spatial and temporal heterogeneity was identified as one of the important factors of In the case of Taiwan, the researchers found that the main metal pollution sources of PM2.5 were coal combustion (34.7%), traffic related emissions (24.2%), secondary aluminum smelting (22.3%) and heavy oil combustion (18.8%), and the concentrations of PM10 and PM2.5 both rise in winter (Hsu, et al, 2016). Several studies on PM2.5 have targeted traffic congestion emissions (Kuo, et al, 2009;Lin, et al, 2015) and detection of metallic composition in urban areas (Chen, et al, 2013). The main pollution sources of PM2.5 in Kaohsiung are traffic exhaust gas, secondary aerosol, and outdoor combustion (agricultural burning and garbage incineration), etc.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…El efecto climático se produce tanto de una manera directa por fenómenos de absorción y dispersión de la radiación solar como, indirectamente, al funcionar como núcleos de condensación que modifican las propiedades radiativas y la persistencia de las nubes 1,2,3 . Los efectos en la salud humana se deben al hecho de que los aerosoles inferiores a 10 μm pueden ser fácilmente inhalados y por lo tanto son potencialmente dañinos para las funciones tanto pulmonares como cardiovasculares 3,4,5,6 . Además se depositan en todos lados dañando toda clase de construcciones y costando millones de dólares en daños a largo plazo.…”
Section: Introductionunclassified